Evaluating the technical and economic feasibility of large scale municipal solid waste to energy project in RSA - Atlantis Foundries anaerobic digestion project case study - Shmulevich, Yoav (Energy Research Centre, 2017)
This dissertation investigates the tech no economic feasibility of a large scale municipal solid waste (MSW) to energy project in the Republic of South Africa, by evaluating the feasibility of Atlantis Foundries (AF) envisaged anaerobic digestion project. Following an audit on the AF site and consultations with AF and Anaergia (PTY) Ltd (the envisaged project technology provider), the most suitable project scenarios under various assumptions were identified and used in the analysis of this study. The feasibility of 2MW continuous, 3MW continuous, 5MW continuous, 5MW peak and standard, 5MW peak and lOMW peak, MSW to energy generation project scenarios were investigated. For each scenario a basic process design was made. A dedicated techno economic model was developed, and parameters obtained from the site audit and design stages were input to the model. Results of the feasibility study were then evaluated and compared with each other. Results showed that all the project scenarios are technically feasible, legally achievable and financially feasible with payback times below 10 years and IRR above 10%. The 5MW peak and standard generation scenario is the most economically attractive option with a payback time of 5.2 years and IRR of 23%, followed by the 5MW continuous generation scenario with a payback time of 5.7 years and IRR of 21%. The 5MW peak and standard generation scenario can offset about 134,000 tonnes of CO2 equivalent GHG emissions per year.